Low frequency of cigarette smoking and the risk of head and neck cancer in the INHANCE consortium pooled analysis - Berthiller, Julien; Ramroth, Heribert (International journal of epidemiology, 2016)
Abstract. Background: Cigarette smoking is a major risk factor for head and neck cancer (HNC). To our knowledge, low cigarette smoking (<10 cigarettes per d